Invasion inhibition in pancreatic cancer using the oral iron chelating agent deferasirox - Shogo Amano (BMC Cancer, 2020)
Abstract Background Iron is required for cellular metabolism, and rapidly proliferating cancer cells require more of this essential nutrient. Therefore, iron regulation may well represent a new avenue for cancer therapy. We have reported, through in vitro and in vivo research involving pancreatic cancer cell lines, that the internal-use, next-generation iron chelator deferasirox (DFX) exhibits concentration-dependent tumour-suppressive effects, among other effects. After performing a microarray analysis on the tumour grafts used in that research, we found that DFX may be able to suppress the cellular movement pathways of pancreatic cancer cells. In this study, we conducted in vitro analyses to evaluate the effects of DFX on the invasive and migratory abilities of pancreatic cancer cells. Methods We used pancreatic cancer cell lines (BxPC-3, Panc-1, and HPAF II) to examine the efficacy of DFX in preventing invasion in vitro, evaluated using scratch assays and Boyden chamber assays. In an effort to understand the mechanism of action whereby DFX suppresses tumour invasion and migration, we performed G-LISA to examine the activation of Cdc42 and Rac1 which are known for their involvement in cellular movement pathways. Results In our scratch assays, we observed that DFX-treated cells had significantly reduced invasive ability compared with that of control cells. Similarly, in our Boyden chamber assays, we observed that DFX-treated cells had significantly reduced migratory ability. After analysis of the Rho family of proteins, we observed a significant reduction in the activation of Cdc42 and Rac1 in DFX-treated cells. Conclusions: DFX can suppress the motility of cancer cells by reducing Cdc42 and Rac1 activation. Pancreatic cancers often have metastatic lesions, which means that use of DFX will suppress not only tumour proliferation but also tumour invasion, and we expect that this will lead to improved prognoses.